Exploring Teachers’ Understanding of Integration of Information and Communication Technology in Teaching Accounting in Umlazi District - Jabulisile Cynthia Ngwenya; Nosihle Veronica Sithole (Journal of Education and Learning Technology)
The purpose of this study was to explore Accounting teachers’ understanding of the integration of Information and Communication Technology (ICT) in teaching Accounting in Umlazi District, South Africa. The literature indicates that ICT has been adopted by the education sector worldwide. To integrate ICT in teaching, teachers must possess knowledge of ICT integration. Hence, this study explored Accounting teachers’ understanding of ICT integration. To complement the literature, the Technological Pedagogical and Content Knowledge (TPACK) theoretical framework informed the empirical inquiry. This study adopted a mixed-methods approach and an explanatory sequential research design to understand the research phenomenon rigorously. Quantitative information was initially collected using a custom-developed questionnaire, followed by qualitative data generated through semi-structured interviews. One hundred and seventy-nine Accounting teachers were randomly sampled for quantitative research, and fourteen were purposively selected for qualitative interviews. Quantitative data was analysed through Statistical Package for the Social Sciences (SPSS), and qualitative data were analysed thematically. The findings indicated that Accounting teachers’ understanding of ICT integration is limited. Findings further indicated that teachers are knowledgeable about smartphones, and they often use them for teaching. Considering the findings, this study recommended that the Department of Basic Education should initiate ICT professional development programmes. Programmes should concentrate on training teachers on practical ICT integration knowledge and skills. Insights from this article will benefit teachers and the Department of Basic Education as they strive to incorporate ICT into their teaching methods while making a timeous contribution to the scholarship of teaching and learning to enhance sustainable digital teaching practices.